In vitro evaluation of the microhardness of bovine enamel exposed to acid solutions after bleaching - Zanet, Caio Gorgulho (2011)
Acid erosion is a superficial loss of enamel caused by chemical processes that do not involve bacteria. Intrinsic and extrinsic factors, such as the presence of acid substances in the oral cavity, may cause a pH reduction, thus potentially increasing acid erosion. The aim of this study was to evaluate the microhardness of bleached and unbleached bovine enamel after immersion in a soda beverage, artificial powder juice and hydrochloric acid. The results obtained for the variables of exposure time, acid solution and substrate condition (bleached or unbleached enamel) were statistically analyzed by the ANOVA and Tukey tests. It was concluded that a decrease in microhardness renders dental structures more susceptible to erosion and mineral loss, and that teeth left unbleached show higher values of microhardness compared to bleached teeth.